2019
DOI: 10.21071/az.v68i264.4989
|View full text |Cite
|
Sign up to set email alerts
|

Estudio morfométrico de pezuñas en genotipos bovinos criados en los humedales del Ñeembucú Paraguay

Abstract: Se evaluó la morfometría de pezuñas en bovinos criados en los humedales del Ñeembucú y áreas de influencia. Participaron 80 hembras adultas agrupadas por genotipos en Criollo Ñeembucú; Criollo Pilcomayo; Nelore; Brahman y Brangus, analizándose Longitud muralla (LM); Altura pezuña (AP); Longitud talón (LT); Longitud pezuña (LP); Diagonal pezuña (DP); Grosor pezuña (GP). El análisis con el software R incluyó varianza paramétrica y no paramétrica, y en las pezuñas anterior medial y posterior lateral, Análisis de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 2 publications
(4 reference statements)
1
10
1
2
Order By: Relevance
“…Despite the adverse climatic conditions in the Andean highlands and the low-quality pastures for feeding the cattle in this region [13], the results obtained for the different biomorphometric parameters were superior to those reported in Creole cattle from different environments such as Mexico [4], Ecuador [3], Panama [9], Uruguay [37], Argentina [38], and Peru [35]. However, other studies conducted in other regions such as those reported for Argentine Creole cattle showed similar results to those obtained in the present study with slightly superior values of BL, RW, and RL [8,13], as well as for the Limonero from Venezuela [33] and the Creole Blanco Orejinegro from Colombia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the adverse climatic conditions in the Andean highlands and the low-quality pastures for feeding the cattle in this region [13], the results obtained for the different biomorphometric parameters were superior to those reported in Creole cattle from different environments such as Mexico [4], Ecuador [3], Panama [9], Uruguay [37], Argentina [38], and Peru [35]. However, other studies conducted in other regions such as those reported for Argentine Creole cattle showed similar results to those obtained in the present study with slightly superior values of BL, RW, and RL [8,13], as well as for the Limonero from Venezuela [33] and the Creole Blanco Orejinegro from Colombia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados son congruentes con la biomecánica del apoyo del pie descrita por Greenough (2009) y con el reporte de Toledo (2006), quién indica que el 90% de las afecciones podales en vacas lecheras se localizaron en el miembro posterior, mayormente en la pezuña lateral. Al respecto, la pezuña lateral del miembro posterior es de mayor dimensión, mientras que, en el miembro anterior corresponde a la pezuña medial (Rodríguez et al, 2019). De igual manera, Perusia (2001) refirió resultados equivalentes con relación al número de casos de patologías en las pezuñas del miembro torácico, aunque mayor en la pezuña medial en relación a la lateral; sin embargo, el recuento de casos en el miembro posterior estuvo por debajo de los valores obtenidos en la presente investigación.…”
Section: Resultados Y Discusiónunclassified
“…En la conformación de las pezuñas se ha destacado el efecto de la genética y la interacción genotipo-entorno como factores que inciden en la adaptación a condiciones ambientales especiales y específicas (Rodríguez et al, 2019). Por otro lado, en la casuística de patologías podales, varios autores han reportado mayor frecuencia sobre las pezuñas laterales del miembro posterior y las mediales del miembro anterior (González y Ramos, 2002; Nan Monte y Galotta, 2006).…”
Section: Introductionunclassified
“…The corporal index was higher than that reported for the Limonero creole bovine from Venezuela (74.3%) [24], the Mixtec creole bovine from Oaxaca (79.9%) [25], the creole bovine Guaymi of Panama (80.52%) [40], the Barroso-Salmeco creole of Guatemala (83.55%) [41], the Casanare creole bovine from Colombia (82.5%) [42], the Saavedra creole bovine from Bolivia (82%) [43], and the creole bovine from the Andean highlands of Peru (82.98%) [44]. However, the corporal index was lower than that reported in Ecuador for the creole bovine from the Province of Azuay (86.8%) [45], the creole bovine from the Province of Huamanga (88.97%) [37], the creole bovine of the Ecuadorian coast (87.5) [46], the creole bovine from Uruguay (88.2%) [47], the creole bovine from the Province of Santa Elena, Ecuador (95.03%) [48], and the creole bovine from the Province of Loja (115.9%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study of the morphometry of structures in animals provides a solid basis to establish allometric relationships between structure and body size, helping to understand the laws of growth [50]. In addition, it allows researchers to know the morphology that the animal has acquired over time and its productive capacities [47]. The external morphology has value as a descriptor, identifier, and differentiator of an individual or breed and allows a greater productive assessment of the animal [51].…”
Section: Discussionmentioning
confidence: 99%